The Strategy of Improving the Performance of Cooperatives in the Review of Organizational Culture, Innovation is Mediated by the Entrepreneurial Orientation in Surabaya - Tri Andjarwati; Endah Budiarti; Beni Agus Setiono (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: The aim of research to proved and analyzed strategy to improve cooperative performance through organizational culture, innovation in mediation with entrepreneurship orientation in surabaya city. Design/methodology/approach: The type of this research was surveying research and the data from questionnaire will be as primer data. Findings: The results showed that organizational culture positive and significant effect against the entrepreneurial orientation, innovation is a positive and significant effect against the entrepreneurial orientation, organizational culture positive and significant effect performance improvement strategies towards cooperative, positive effect not significant innovation strategy improved performance of cooperatives, entrepreneurial orientation effect positive and significant performance improvement strategies against the cooperative. Research limitations/implications: The data collected were declared valid and reliable, then processed for analysis using structural equation model or Structural Equation Modeling (SEM). Practical implications: The population study for this research was all primary cooperatives in Surabaya with total 400 cooperatives that have the following characteristics: (a) has a member of a minimum of 100 people, (b) active of operations and implement RAT for 3 years successively, (c) has more than two business units (d) and has assets of over 1 billion rupiah. The sample for this research was 138 primary cooperation. Originality/value: This paper is original Paper type: Literature review